Dyslexia and foreign language learning - Schneider, Elke (David Fulton, 2003)
Offering strategies and techniques for teaching modern foreign languages - an often severely challenging subject for pupils with dyslexia - this book is specifically designed to meet the needs of the busy subject specialist teacher looking for guidance on supporting pupils.